Virus‐Free and Live‐Cell Visualizing SARS‐CoV‐2 Cell Entry for Studies of Neutralizing Antibodies and Compound Inhibitors. Issue 2 (18th December 2020) - Zhang, Yali; Wang, Shaojuan; Wu, Yangtao; Hou, Wangheng; Yuan, Lunzhi; Shen, Chenguang; Wang, Juan; Ye, Jianghui; Zheng, Qingbing; Ma, Jian; Xu, Jingjing; Wei, Min; et al.
Abstract: The ongoing corona virus disease 2019 (COVID‐19) pandemic, caused by SARS‐CoV‐2 infection, has resulted in hundreds of thousands of deaths. Cellular entry of SARS‐CoV‐2, which is mediated by the viral spike protein and ACE2 receptor, is an essential target for the development of vaccines, therapeutic antibodies, and drugs. Using a mammalian cell expression system, a genetically engineered sensor of fluorescent protein (Gamillus)‐fused SARS‐CoV‐2 spike trimer (STG) to probe the viral entry process is developed. In ACE2‐expressing cells, it is found that the STG probe has excellent performance in the live‐cell visualization of receptor binding, cellular uptake, and intracellular trafficking of SARS‐CoV‐2 under virus‐free conditions. The new system allows quantitative analyses of the inhibition potentials and detailed influence of COVID‐19‐convalescent human plasmas, neutralizing antibodies and compounds, providing a versatile tool for high‐throughput screening and phenotypic characterization of SARS‐CoV‐2 entry inhibitors. This approach may also be adapted to develop a viral entry visualization system for other viruses. Abstract : This study develops a recombinant fluorescent protein (FP)‐fused severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike trimer protein (STG) to probe the viral entry process in angiotensin‐converting enzyme 2‐expressing cells. The new system enables live‐cell visualization of cellular binding, uptake, and intracellular trafficking of SARS‐CoV‐2 in virus‐free conditions. It provides a high‐content analysis tool to reveal the detailed influence of SARS‐CoV‐2 entry inhibitors, including antibodies and compounds.